2011
DOI: 10.1088/0031-8949/84/03/035803
|View full text |Cite
|
Sign up to set email alerts
|

Protonic transport through solitons in hydrogen-bonded systems

Abstract: We offer an alternative route for investigating soliton solutions in hydrogen-bonded (HB) chains. We invoke the modified extended tangent hyperbolic function method coupled with symbolic computation to solve the governing equation of motion for proton dynamics. We investigate the dynamics of proton transfer in HB chains through bell-shaped soliton excitations, which trigger the bio-energy transport in most biological systems. This solitonic mechanism of proton transfer could play functional roles in muscular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Proton motion is known to be responsible for the energy and charge transfer in many HB chains [44]. The conduction via proton migration along the chain in HB systems appears as:…”
Section: Mathematical Background Of Proton Dynamicsmentioning
confidence: 99%
“…Proton motion is known to be responsible for the energy and charge transfer in many HB chains [44]. The conduction via proton migration along the chain in HB systems appears as:…”
Section: Mathematical Background Of Proton Dynamicsmentioning
confidence: 99%
“…Kavitha et al also reported the solitonic dynamics of the chain polarization in HB systems, when tunnel processes prevail over the thermal activation and analyzed the tunneling between two opposite directions governed by a bistable potential system at low temperature [2,5]. They suggested a possible coherent tunneling mechanism of spontaneous polarization oscillations of HB chain.…”
Section: B(x T)mentioning
confidence: 99%
“…A special property of PGs is their ability to form HBs [2] with each other, and with water and other molecules in the environment. The study of HB chains [3][4][5] can lead to insight regarding how local interactions can dictate global features of PCs and proteins. Basically, PCs of protein structures [6] are the major workers within the cells, and carry out the functions described by the genetic codes: providing structural support, transmitting signals, catalyzing reactions, and transporting molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently Soliman (Soliman, 2006) and El-Wakil (El-Wakil et al, 2005) modified the extended tanh-function method and obtained some new exact traveling wave solutions. We employ the modified extended tanh-function (METF) method (Soliman, 2006;El-Wakil et al, 2005;Kavitha et al, 2011bKavitha et al, , 2012 to solve the Eq. 12which governs the dynamics of director oscillations with elastic deformations such as splay, twist and bend.…”
Section: Shape Changing Solitary Oscillationsmentioning
confidence: 99%